PERSEPSI PENGUNJUNG PADA FASILITAS OBYEK WISATA SUNGAI GELOMBANG DI DESA SIPUNGGUK KAMPAR RIAU - Afriliana, Rissa; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Facilities are facilities and infrastructure that support the operations of tourist attractions to accommodate all tourist needs, do not directly encourage growth but develop at the same time or after the attraction develops. In this case, facilities can be divided into main, supporting and ancillary facilities. This research aims to determine the facilities of the Wave River tourist attraction in Sipungguk Village, Kampar Regency, Riau Province and to determine visitor perceptions of the facilities of the Wave River tourist attraction. In this research, the author used quantitative methods as a data processing procedure. The data processing techniques used were observation, questionnaires and documentation using a Likert scale as a measuring tool. Based on the research results, the facilities at the Wave River tourist attraction in Sipungguk Village, Kampar Regency, Riau Province, are in the good category. Key words: perception, visitors, facilities.